1983
DOI: 10.1177/001316448304300431
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure on the Adult Nowicki-Strickland I-E Scale in a College Population

Abstract: The purpose of the present study was to identify the factor structure of the Adult Nowicki-Strickland I-E Scale (ANS-IE) and to compare the results with those in a 1976 publication by Dixon, McKee, and McRae. The sample consisted of 174 subjects obtained from a college population. Both a two-factor and four-factor solution were obtained. Differential factor dimensionality was indicated for males and females. Further, the results revealed a high degree of similarity for Factor I items on the ANS-IE in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Many of the original measurement procedures used to instantiate the construct have been criticized on the grounds that the full range of social contexts (e.g., political, social, academic, business) in which locus of control operates was not adequately sampled (cf. Coombs & Schroeder, 1988;Piotrowski, Dunn, Sherry, & Howell, 1983). Another controversy concerns the domain specificity of locus of control indices (Rotter, 1975).…”
mentioning
confidence: 99%
“…Many of the original measurement procedures used to instantiate the construct have been criticized on the grounds that the full range of social contexts (e.g., political, social, academic, business) in which locus of control operates was not adequately sampled (cf. Coombs & Schroeder, 1988;Piotrowski, Dunn, Sherry, & Howell, 1983). Another controversy concerns the domain specificity of locus of control indices (Rotter, 1975).…”
mentioning
confidence: 99%
“…Cognitive models of depression hypothesize that maladaptive controlrelated beliefs precede depression and are relatively stable (34); if this is so, then individuals at risk for depression could conceivably be identified using attributional measures. Attribution-oriented therapy has been suggested as a means of treating and even preventing depression (20).…”
Section: Discussionmentioning
confidence: 99%
“…The items are divided equally into three factors measuring belief in Internal, Powerful Others, and Chance control. As the locus of control construct appears to be multidimensional (24,27,34), Levenson's approach may have greater explanatory power than the unidimensional Rotter Internal-External scale (36) or the Nowicki-Strickland Internal-External scale (30). Levenson (21) reported internal consistency estimates of .67 (Internal), .79 (Chance), and .82 (Powerful Others).…”
Section: Methodsmentioning
confidence: 99%
“…Factor II was concerned with luck for males and futility of effort for females. Piotrowski, Dunn, Sherry and Howell (1983) reported that four factors accounted for 50.7% of the variance. Finch, Kendall, Spirito and Mikulka (1981) found evidence of a five factor solution.…”
Section: Validitymentioning
confidence: 99%
“…Similarly, Kearney and Kearney (1983) used two small samples (86 males and 108 females) and reported a different factor structure for males and females. Finally, Piotrowski et al (1983) performed a factor analysis on a sample of 71 respondents, yielding four factors. In all these studies, however, the sample size was below the recommended number of 200 suggested by Guilford (1954), indicating that the solutions proposed might not be replicated in another sample.…”
Section: Validitymentioning
confidence: 99%